Taman Ramah Anak sebagai Sistem Ruang Adaptif dalam Pengembangan Desa Wisata Ramah Anak Berkelanjutan - Muhammad Ismail Hasan; Ika Zenita Ratnaningsih; Adi Firman Ramadhan; Chely Novia Bramiana; Mokhamad K. Husodo (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Universitas Pradita, 2026)
This study aims to solve the problem lack of children-friendly park to support children’s sensory and motor development, as well as their social interaction, in Karangtengah Village, Tuntang District, Semarang Regency, while also serving as a pilot model for a child-friendly village initiative. The planning of this tourism village is part of a thematic community service program conducted by Universitas Diponegoro, involving participants from multidisciplinary backgrounds. The program began with a preliminary survey in Karangtengah Village to identify physical potential, including location, natural resources, and infrastructure. A Focus Group Discussion (FGD) was then conducted with village representatives to further explore additional potentials, such as culture, arts, community organizations, and human resources. The results of the survey and FGD revealed the presence of a green open space with strong potential to be developed as a tourism site. Women’s community organizations, such as Posyandu and PKK, have positioned child-friendliness as the main theme of the tourism village, thereby stimulating local economic development while also promoting children’s health in Karangtengah Village. This study provides valuable insights for planners and local government authorities in designing and developing tourism villages, particularly in terms of child-friendly infrastructure that supports children’s well-being.